Student’s Language Problems in Communicating during Learning - Syahrin, Alfi; Naila Zavira; Rizana (International Journal of Educational and Psychological Sciences, 2023)
This study aims to reveal students' languageproblems in communicating during learning. This research uses qualitative research with grounded theory type. The data of this research are in the form of words and sentences. The results of the study illustrate that the problems of speaking Indonesian during the teaching and learning process are caused by a lack of awareness of students to use Indonesian, so that there is a lack of knowledge about vocabulary in Indonesian. In this case, the teacher plays a very important role in guiding them to get to know the Indonesian language first. In the context of education, language has an important role because of its potential impact on student achievement when exposed to a particular  teaching program.